2018
DOI: 10.1186/s13104-018-3459-6
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to achieving low palatal fistula rates following primary cleft palate repair: experience of an institution in Uganda

Abstract: ObjectiveTo determine frequency of palatal fistula following primary cleft palate repair and the associated factors as a measure of cleft palate repair outcome and its challenges at a cleft centre in Uganda.ResultsBetween May and December 2016, 54 children with cleft palate were followed up at Comprehensive Rehabilitation services of Uganda (CoRSU) hospital, from time of primary cleft palate repair until at least 3 months postoperative to determine whether they developed palatal fistula or not. Frequency of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
3
17
1
Order By: Relevance
“…In that study, 10/15 (67%) severely underweight children had a postoperative fistula, compared to 4/13 (31%) underweight children and 5/26 (19%) of nonunderweight children. However, as noted above, in that study, 24% of patients were underweight, and 15% were severely underweight by WHO standards, compared to the lower numbers of each seen in our patient population 21 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In that study, 10/15 (67%) severely underweight children had a postoperative fistula, compared to 4/13 (31%) underweight children and 5/26 (19%) of nonunderweight children. However, as noted above, in that study, 24% of patients were underweight, and 15% were severely underweight by WHO standards, compared to the lower numbers of each seen in our patient population 21 …”
Section: Discussionsupporting
confidence: 83%
“…One study from England by Pandya et al, of 147 patients found that 38% of patients with CLP had failure to thrive at the time of surgery, 20 whereas a study from Uganda by Cubitt et al, of 243 patients noted that, on average, patients with cleft lip and palate had a WFA Z‐score of −3.21 at time of surgery, compared to a WFA Z‐score of 0.99 in a group of 78 children without CLP undergoing different procedures 15 . Another study in Uganda by Katusabe et al, of 78 children with cleft palate found 24% were underweight and 15% were severely underweight by WHO standards of WFA at the time of surgery 21 . A recent study from Brazil found that 12.9% of all patients with CLP under the age of two were acutely malnourished, and 14.4% chronically malnourished using WHO growth standards 22 …”
Section: Discussionmentioning
confidence: 99%
“…One of the indicators of successful cleft palate repair is a reduced incidence of palatal fistula. 19.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported absence of fistula development after cleft palate repair that supports our results. 19,20 This could be linked to the exclusion of patients with very wide palatal clefts and smaller number of the study group. Some studies reported that fistula rate was higher for the more sever degree of clefting.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge in cleft care in SSA is malnutrition, which prevents the opportunity to receive care if the patient is in such poor condition that they are not a surgical candidate (Massenburg et al, 2016). Of note, if cleft palate repairs are performed in malnourished patients, there is an increased risk of palatal fistula postsurgery (Katusabe et al, 2018). Additionally, patients often do not have the financial resources to seek care (Massenburg et al, 2016;Bello et al, 2018).…”
Section: Current Infrastructure and Limitations Of Cleft Repairmentioning
confidence: 99%